Nonlinear Coupling Between Whistler‐Mode Chorus and Electron Cyclotron Harmonic Waves in the Magnetosphere. Issue 23 (9th December 2018) - Gao, Zhonglei; Su, Zhenpeng; Xiao, Fuliang; Summers, Danny; Liu, Nigang; Zheng, Huinan; Wang, Yuming; Wei, Fengsi; Wang, Shui
Abstract: Electromagnetic whistler‐mode chorus and electrostatic electron cyclotron harmonic (ECH) waves can contribute significantly to auroral electron precipitation and radiation belt electron acceleration. In the past, linear and nonlinear wave‐particle interactions have been proposed to explain the occurrences of these magnetospheric waves. By analyzing Van Allen Probes data, we present here the first evidence for nonlinear coupling between chorus and ECH waves. The sum‐frequency and difference‐frequency interactions produced the ECH sidebands with discrete frequency sweeping structures exactly corresponding to the chorus rising tones. The newly generated weak sidebands did not satisfy the original electrostatic wave dispersion relation. After the generation of chorus and normal ECH waves by hot electron instabilities, the nonlinear wave‐wave interactions could additionally redistribute energy among the resonant waves, potentially affecting to some extent the magnetospheric electron dynamics. Plain Language Summary: Whistler‐mode chorus and electron cyclotron harmonic emissions are two distinct magnetospheric waves responsible for auroral electron precipitation and radiation belt electron acceleration. How these magnetospheric waves are generated has remained an outstanding question. They were usually explained as a result of linear and nonlinear wave‐particle interactions in early studies. By analyzing the high‐resolution data of Van Allen Probes, we present here the first evidence for nonlinear coupling between chorus and electron cyclotron harmonic emissions. Such nonlinear wave‐wave interactions could transfer energy among the resonant waves and affect the magnetospheric electron dynamics. This new finding will be of high interest to the communities of space plasma physics and magnetospheric physics. Key Points: Nonlinear resonant interactions between chorus and electron cyclotron harmonic waves occurred around the magnetic equator Newly generated ECH sidebands exhibited frequency sweeping structures and failed to satisfy the original linear dispersion relation After the hot electron instabilities, the nonlinear wave‐wave interactions could additionally redistribute energy among the resonant waves